Early Outcome of Liver Resections in Octogenarians - Bhandari, RS; Riddiough, G; Muralidharan, V; Christophi, C (Kathmandu University Medical Journal, 2015)
Background Reports on safety and feasibility of liver resection in patients 80 years and older are very limited.Objective Here, we intend to analyze the perioperative outcomes of liver resections in octogenarians performed at a single tertiary level teaching hospital over a ten years period.Method Retrospective review of the medical records (between 2004 to 2014) of patients of the defined age group was performed. Clinicopathological features, indications, extent of resections, intraoperative parameters, postoperative complications and final outcome were analyzed. Findings were compared with similar studies published in literature.Result Total 19 (11 male, 8 female, maximum age 85 years) patients of the study group underwent liver resection during the defined period. Commonest indication was colorectal liver metastasis (9 patients). One patient had pancreaticodudenectomy for periampullary malignancy four years prior to present with liver metastasis and subsequently had liver resection for recurrence of disease. Except one, all had open surgery. Types of resection ranged from sub segmental to major right (8 patients) and left (1 patient) hepatectomy. Total 3 (27%) out of 11 patients on whom drain was not placed required radiological drainage of abdominal collection. One patient developed liver abscess postoperatively and was also successfully drained under radiological guidance. Only 2 (10.5%) had prolonged Intensive Care Unit (ICU) stay and remaining patients were discharged to ward after 24 hrs of observation in high dependency/Intensive care unit. Median hospital stay was 11 days. Postoperative complications were 3 of grade II, 4 of grade IIIa, 1 of IIIb and 2 of IVa. Total 9 patients were discharged to rehabilitation centers and remaining 10 could be discharged home. There was 0% mortality.Conclusion In appropriately selected cases, when performed in specialized tertiary centers excellent perioperative outcomes of liver resections can be achieved even in patients of 80 years of age and above.Kathmandu University Medical Journal Vol.13(1) 2015; 19-23